Low bone mineral density as a risk factor for osteoporosis and ways of its correction in male patients with ankylosing spondylosis - O. A. Pirogova; T. A. Raskina; M. V. Letaeva (Современная ревматология, 2014)
Objective: to estimate bone mineral density (BMD) in men with ankylosing spondylosis (AS).Subjects and methods. Seventy-two male patients (mean age 43.2±9.1 years) diagnosed with extended- or late-stage AS (according to the 1984 modified New York criteria) (a study group) were followed up. A control group consisted of 70 apparently healthy men of the same age (46.7±1.9 years) with neither a history of bone fractures and no complains about osteoporosis (OP). In the study and control groups, BMD was determined by dual-energy X-ray absorptiometry.Results. The patients with AS were found to have statistically significantly lower BMD in the femoral neck and lumbar spine. In the study group, osteopenic syndrome (OPS) was identified in 44 (61.1%): osteopenia (OPe) in 16 (22.2%) and OP in 28 (38.9%). In the control group, OPS was detected in 16 (21.62%) patients, OPe in 12 (16.21%), and OP in 4 (5.40%). Lower BMD was noted in both the femoral neck and lumbar spine in the extended stage of AS and only in the femoral neck in its late stage.